2.6 BLOOD PRESSURE-INDEPENDENCE OF AORTIC-TO-BRACHIAL ARTERY STIFFNESS RATIO IS DEPENDENT ON DISEASE STATUS - Matthew K. Armstrong; Martin G. Schultz; Dean S. Picone; James E. Sharman (Artery Research, 2017)
Introduction: Aortic stiffness predicts cardiovascular mortality but is limited as a risk marker because it is dependent on blood pressure (BP). A potential solution is provided from the ratio of aortic-to-brachial artery stiffness (ab-ratio), which is purported to be a BP-independent risk marker among patients with renal dysfunction (RD). We sought to determine the BP-independence of the ab-ratio in patients with disease (including RD) and healthy populations. Methods: The ab-ratio (aortic/brachial pulse wave velocity; PWV) and mean arterial pressure (MAP) were recorded in patients with RD (n = 119, aged 65 ± 7 years), hypertension (n = 140, aged 62 ± 9 years), type 2 diabetes (n = 77, aged 60 ± 9 years) and healthy individuals (n = 99, aged 51 ± 8 years). Multiple-regression analysis was performed to test the independent association of MAP with the ab-ratio adjusted for age, sex, body-mass index and blood glucose. Results: There was no significant relationship between the ab-ratio and MAP in patients with RD (β = 0.002, 95% CI 0.002, 0.006, p = 0.34), hypertension (β = 0.001, 95% CI 0.003, 0.006, p = 0.62) or diabetes (β = 0.006, 95% CI 0.002, 0.014, p = 0.11). However, in healthy individuals the ab-ratio was significantly and independently associated with MAP (β = 0.008, 95% CI 0.003, 0.013, p = 0.003). There was a significant difference in the strength of association between the ab-ratio and MAP between patients with disease and healthy individuals (z > 2.2, p < 0.05 for all). Conclusion: Although ab-ratio is purported to be a risk marker that is independent of BP, this was observed only among patient populations, and not in healthy individuals. Therefore, the ab-ratio is influenced by disease status and may have restricted value as a BP-independent risk marker.